The dispute about the scientific nature of eugenics - Słoniowska, Anna (Studia Ecologiae et Bioethicae, 2016)
How to classify eugenics? Is it an ideology, outlook, or maybe a science? These are the questions asked by philosophers and historians for a long time, but there is still no answer. Even the people who created this idea did not know how to specify it. They wanted to characterize eugenics as science, but the problems with logic and methodology increased. They made a formal fallacy and entrusted too much to induction. The lack of knowledge about heredity was also a serious problem. For all that, they tried to create a new scientific theory based on eugenics. Recently, most historians claim that old eugenics failed, however some have a different opinion. It seems that this view depends on individual’s emotional and subjective assessment of modern researchers.